Comparison of Lateralizing Calcaneal Osteotomies for Varus Hindfoot Correction. (October 2018) - An, Tonya W.; Michalski, Max; Jansson, Kyle; Pfeffer, Glenn
Background: There is limited consensus on the optimal operative technique for correcting heel varus in patients with Charcot-Marie-Tooth (CMT) disease. This comparative study evaluated the ability of 4 lateralizing calcaneal osteotomies, with and without Dwyer wedge resection and coronal rotation of the posterior tuberosity, to correct severe heel varus. Methods: The computed tomography (CT) scan of a teenage CMT patient with severe hindfoot varus was used to create 3-dimensional (3D)–printed models of the talus, calcaneus, and cuboid. A custom jig facilitated precise replication of the osteotomy cuts. Four different configurations were created: oblique osteotomy with lateralization, oblique osteotomy with lateralization and internal rotation of the posterior tuberosity, Dwyer wedge resection with lateralization, and Dwyer wedge resection with lateralization and internal rotation. CT scans were performed on each model before and after osteotomy. Statistical analysis was used to evaluate differences in several predefined radiographic parameters. Results: The sequential transformations generated increasing lateral translation of the weight-bearing calcaneus. Dwyer wedge osteotomy significantly improved lateralization (effect = 8.0 mm), valgus hindfoot angle (effect = 6.1 degrees), and coronal calcaneal tilt (effect = −17.6 degrees) compared with the oblique osteotomy. Internal rotation of the posterior tuberosity further improved lateralization (effect = 3.3 mm), valgus hindfoot angle (effect = 2.5 degrees), and coronal calcaneal tilt (effect = −11.7 degrees). Dwyer osteotomy models had on average 5-mm shorter posterior tuberosity lengths than the oblique osteotomies. The addition of rotation did not significantly affect length. Conclusions: Significant lateralization of the posterior tuberosity was achieved in all transformations. The Dwyer wedge osteotomy improved hindfoot valgus angle, coronal calcaneal tilt, and lateralization of the weight-bearing surface compared with oblique osteotomy. Posterior tuberosity internal rotation further lateralized the plantar surface and normalized weight bearing. Lateralization, combined with Dwyer osteotomy and coronal plane internal rotation, achieved the greatest correction of varus heel. Clinical Relevance: This study compares multiple lateralizing calcaneal osteotomies and proposes a combined technique of lateralization, Dwyer wedge resection, and coronal plane rotation to address advanced cavovarus hindfoot deformities.